Photoinduced Release of Neurotransmitter Amino Acids from Coumarin‐Fused Julolidine Ester Cages. Issue 34 (9th October 2013) - Piloto, Ana M.; Hungerford, Graham; Costa, Susana P. G.; Gonçalves, M. Sameiro T.
Abstract: The photoinduced release of several neurotransmitter amino acids (glycine, alanine, glutamic acid, β‐alanine and γ‐aminobutyric acid) was accomplished from ester cages based on a new photoremovable protecting group consisting of a coumarin built on the julolidine nucleus, namely a (11‐oxo‐2, 3, 5, 6, 7, 11‐hexahydro‐1 H ‐pyrano[2, 3‐ f ]pyrido[3, 2, 1‐ ij ]quinolin‐9‐yl)methyl group. Photolysis and steady‐state sensitization studies revealed that release of the active molecule occurred in short irradiation times at long wavelengths, with a very promising performance at 419 nm. Given the interest in the development of novel protecting groups that are cleavable with UV A or even visible radiation, it was found that a structural modification in the coumarin ring by assembly of a fused julolidine leads to a promising photolabile protecting group for organic synthesis and also for bioapplications. Abstract : Photolysis and steady‐state sensitization studies of several neurotransmitter amino acids from ester cages based on a new photoremovable protecting group consisting of a coumarin‐fused julolidine nucleus, revealed that the release of the active molecule occurred in short irradiation times at long wavelengths, especially at 419 nm.